Analyzing economic feasibility for investing in nursing care: Evidence from panel data analysis in 35 OECD countries - Arshia Amiri; Tytti Solankallio-Vahteri (Elsevier, 2020)
Objective: To analyze economic feasibility for investing in nursing care. Method: The number of practicing nurses' density per 1000 population as a proxy for nursing staff and Gross Domestic Product (GDP) per capita (current US$) were collected in 35 member countries of Organization for Economic Co-operation and Development (OECD) over 2000-2016 period. The statistical technique of panel data analysis including unit root test, cointegration analysis, Granger causality test, dynamic long-run model analysis and error correction model were applied to measure economic impact of nursing-related services. Results: There was a committed bilateral relationship between nurse-staffing level and GDP with long-run magnitudes of 1.39 and 0.41 for GDP-lead-nurse and nurse-lead-GDP directions in OECD countries, respectively. Moreover, the highest long-run magnitudes of the effect nursing staff has on increasing GDP per capita were calculated in Finland (2.07), Sweden (1.92), Estonia (1.68), Poland (1.52), Czech Republic (1.48), Norway (1.47) and Canada (1.24). Conclusion: Our findings verify that although the dependency of nursing characteristics to GDP per capita is higher than the reliance of GDP to number of nurses' density per 1000 population, investing in nursing care is economically feasible in OECD countries i.e. nursing is not only a financial burden (or cost) on health care systems, but also an economic stimulus in OECD countries. Hence, we alert governments and policy makers about the risk of underestimating the economic impacts of nurses on economic systems of OECD countries. Keywords: Gross Domestic Product, Economic growth, Nursing economics, Nursing services, Nursing staff, Organization for Economic Co-operation and Development, Panel data analysis